1989
DOI: 10.1093/iclqaj/38.2.321
|View full text |Cite
|
Sign up to set email alerts
|

Human Rights and Humanitarian Intervention: The Case Law of the World Court

Abstract: THIS article briefly canvasses a small number of International Court of Justice cases in which the Court has addressed human rights issues. From this it emerges that the Court has unambiguously accepted that the obligation to respect fundamental human rights is an obligation found in general international law. Questions may, however, remain as to: (1) whether all the human rights enumerated in the Universal Declaration of Human Rights are equally binding; (2) whether the content of all the rights may be equall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The Economic and Social Council confirmed that the scope of this term 'should not go beyond intentional crimes, with lethal or other extremely grave consequences' in the Safeguards Guaranteeing Protection of the Rights of Those Facing the Death Penalty [23]. Any intentional crimes which infringe life appear to be 'most serious crimes' and apply the death penalty [24]. The 'other extremely grave consequences' appear to indicate that other circumstances, e.g., circulation of 'secret information to an enemy in wartime', may lead to large-scale loss of life [25].…”
Section: Negative Commentsmentioning
confidence: 99%
“…The Economic and Social Council confirmed that the scope of this term 'should not go beyond intentional crimes, with lethal or other extremely grave consequences' in the Safeguards Guaranteeing Protection of the Rights of Those Facing the Death Penalty [23]. Any intentional crimes which infringe life appear to be 'most serious crimes' and apply the death penalty [24]. The 'other extremely grave consequences' appear to indicate that other circumstances, e.g., circulation of 'secret information to an enemy in wartime', may lead to large-scale loss of life [25].…”
Section: Negative Commentsmentioning
confidence: 99%
“…60 See Article 38 of the ICJ Statute; Schachter, Oscar. 66 The American Journal of International Law : 337-351;Rodley, Nigel S. 1989. International law in theory and practice , 35.…”
Section: International Competencementioning
confidence: 99%
“…180 Gradually, the focus shifted to examining directly the impact of human rights on other areas of international law. These included areas such as humanitarian intervention, 181 customary international law, 182 treaties 183 and international humanitarian law, 184 as well as international law more generally. 185 It also extended to understanding the development of international criminal law, 186 comparative human rights, 187 and private international law.…”
Section: Human Rights and International And Comparative Lawmentioning
confidence: 99%